1994
DOI: 10.1063/1.111778
|View full text |Cite
|
Sign up to set email alerts
|

New approach to the growth of low dislocation relaxed SiGe material

Abstract: In this growth process a new strain relief mechanism operates, whereby the SiGe epitaxial layer relaxes without the generation of threading dislocations within the SiGe layer. This is achieved by depositing SiGe on an ultrathin silicon on insulator (SOI) substrate with a superficial silicon thickness less than the SiGe layer thickness. Initially, the thin Si layer is put under tension due to an equalization of the strain between the Si and SiGe layers. Thereafter, the strain created in the thin Si layer relaxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
105
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(105 citation statements)
references
References 7 publications
0
105
0
Order By: Relevance
“…Transmission electron microscopy observations have demonstrated a reduced dislocation density of films grown to many times their Matthews-Blakeslee 2 critical thickness h c on glass-bonded compliant substrates. [3][4][5] High-resolution x-ray diffraction ͑HRXD͒ measurements and atomic-force microscopy characterization were carried out on thick ͑3 m͒, highly mismatched ͑3%͒ In 0.45 Ga 0.55 As films grown simultaneously on conventional and the compliant substrates that are the focus of the present study. These measurements demonstrated a ϳ2ϫ reduction in the breadth of the film's strain distribution as determined by triplecrystal diffraction peak widths that decreased from 270Љ on a conventional substrate to 155Љ on the glass-bonded substrate.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Transmission electron microscopy observations have demonstrated a reduced dislocation density of films grown to many times their Matthews-Blakeslee 2 critical thickness h c on glass-bonded compliant substrates. [3][4][5] High-resolution x-ray diffraction ͑HRXD͒ measurements and atomic-force microscopy characterization were carried out on thick ͑3 m͒, highly mismatched ͑3%͒ In 0.45 Ga 0.55 As films grown simultaneously on conventional and the compliant substrates that are the focus of the present study. These measurements demonstrated a ϳ2ϫ reduction in the breadth of the film's strain distribution as determined by triplecrystal diffraction peak widths that decreased from 270Љ on a conventional substrate to 155Љ on the glass-bonded substrate.…”
mentioning
confidence: 99%
“…There have been numerous descriptions in the literature of the effect of an ''elastically compliant substrate'' on film strain during growth. 3,4,[6][7][8][9][10][11][12][13] The strain in the film ⑀ f in terms of the film thickness h f , the template layer thickness h s , and the mismatch ⑀ 0 , between the film and substrate due to elastic compliance of the template layer is described by ⑀ f ϭ ⑀ 0 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two approaches to fabricating macroscopic compliant substrates have predominated. The first utilized a metal 7 or glass [8][9][10][11] media to join the template and handle. The second approach employed twist-bonded ͑TB͒ substrates, 12,13 in which the template was directly bonded to the handle with an intentional azimuthal angular misorientation .…”
mentioning
confidence: 99%
“…Several studies utilizing transmission electron microscopy ͑TEM͒ have demonstrated a reduced dislocation density over sub-micron-sized areas of films when grown on glass-bonded [8][9][10] and twist-bonded 12,13 compliant substrates. There are comparatively little high-resolution x-ray diffraction ͑HRXD͒ data which measures the film relaxation behavior over macroscopic dimensions.…”
mentioning
confidence: 99%